2020
DOI: 10.1021/acssensors.0c00444
|View full text |Cite
|
Sign up to set email alerts
|

Surface Enhanced Raman Spectroscopy Based Biosensor with a Microneedle Array for Minimally Invasive In Vivo Glucose Measurements

Abstract: Surface enhanced Raman spectroscopy based biosensor with a microneedle array for minimally invasive in vivo glucose measurements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 58 publications
0
67
0
Order By: Relevance
“…In another work, NOA MNs were functionalised with plasmonically active gold nanorods and covered with the pH-sensitive molecule 4-mercaptobenzoic acid to use in Surface Enhanced Raman Spectroscopy (SERS) [95]. SERS was implemented with PMMA MN coated by silver nanoparticles and functionalised with 1-decanethiol [96]. The PMMA MN array was prepared using a stainless-steel master mould.…”
Section: Casting Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, NOA MNs were functionalised with plasmonically active gold nanorods and covered with the pH-sensitive molecule 4-mercaptobenzoic acid to use in Surface Enhanced Raman Spectroscopy (SERS) [95]. SERS was implemented with PMMA MN coated by silver nanoparticles and functionalised with 1-decanethiol [96]. The PMMA MN array was prepared using a stainless-steel master mould.…”
Section: Casting Methodsmentioning
confidence: 99%
“…Solid MNs were generally functionalised to serve as bio-electrodes and sometimes to punch the skin [91]. The fabrication techniques that were reported for producing solid MNs are 1) casting [82,[92][93][94][95][96][97][98][99][100][101]; 2) injection moulding [83,[102][103][104][105][106][107], Figure 3A; 3) DRIE [84,[108][109][110], Figure 3B, and 4) wet chemical etchant [85,111], Figure 3C. Solid MNs for ISF sampling were also fabricated using infrared laser [112] and lithographically defined chemical etching [113].…”
Section: Solid Mnsmentioning
confidence: 99%
“…Sharma et al 137 , however, reported that their device with a PP film required application for an hour to allow the sensor to equilibrate with ISF and achieve a stable baseline before readings could be taken. Surface-enhanced Raman spectroscopy (SERS) has also been used in conjunction with solid metal-coated microneedles for the in-situ detection of glucose, pH and the hemozoin, a metabolite of haemoglobin produced by malaria parasites in infected erythrocytes 137 , 146 , 147 , 148 . The mechanism of SERS is apparently related to the frequency of monochromatic light changes on a surface based on the interactions with a molecule where the resulting signal is subsequently enhanced using metal nanoparticles 149 .…”
Section: Microneedle Diagnostic Platformsmentioning
confidence: 99%
“…62 To improve the extraction and detection efficiencies, MNs with novel microstructures or materials can be prepared by a multi-step process. [63][64][65][66][67] For example, Mandal et al designed a MN patch with a core-shell structure for longitudinal sampling of cells and skin ISF. The group rst fabricated polylactic acid (PLA) MN arrays through PDMS molds and subsequently coated them with polylysine, alginate, and sucrose mixtures.…”
Section: Design and Fabrication Strategies Of Mnsmentioning
confidence: 99%